ANALISIS KINERJA PENGELOLAAN ZAKAT DALAM ASPEK MANAJEMEN SYARIAH: Pada BAZNAS Kabupaten Tebo - Deni Yulia Citra; Efni Anita; Aztyara Ismadharliani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the performance of zakat management at the National Zakat Amil Agency (BAZNAS) in Tebo Regency, with a focus on alignment with sharia management principles. This research identifies several important factors that contribute to suboptimal management of zakat funds, including a lack of public awareness about BAZNAS, low public participation in zakat distribution, and significant geographic challenges that hinder access to zakat services. Interviews with key stakeholders revealed that many individuals prefer to give zakat directly to recipients, which undermines BAZNAS' effectiveness in managing these funds. This study highlights the need for increased outreach and educational initiatives to increase awareness and encourage community involvement in zakat programs. Additionally, this underlines the importance of establishing regional regulations to promote zakat contributions through BAZNAS. The findings show that overcoming these challenges is critical to improving zakat management and maximizing its benefits to society.